Allergic Airway-Induced Hypersensitivity Is Attenuated by Bergapten in Murine Models of Inflammation - Douglas B. Aidoo; David D. Obiri; Newman Osafo; Aaron O. Antwi; Leslie B. Essel; Babatunde M. Duduyemi; Martins Ekor (Hindawi Limited, 2019)
Bergapten (5-methoxypsoralen, 5-MOP) is a plant-derived furocoumarin with demonstrated anti-inflammatory action. The present study investigated its effects on allergic inflammation in two related pathways of mast cell degranulation. Compound 48/80 and lipopolysaccharide (LPS) were used to activate the IgE-independent pathway while bovine serum albumin (BSA) was used as allergen for the IgE-dependent pathway. The modulatory effect of bergapten on mast cell degranulation, neutrophil extravasation, protein concentration, lung histopathology, and oxidative stress was assessed. Bergapten at 10, 30, and 100 μg/ml for 15 min stabilized mast cells in rat mesenteric tissue from disruption in vitro and when administered in vivo at 3, 10, and 30 mg kg−1 for 1 h protected mice from fatal anaphylaxis induced by compound 48/80. Similarly, treatment of LPS-challenged mice with bergapten (3, 10, and 30 mg kg−1) for 24 h significantly decreased neutrophil infiltration into bronchoalveolar lavage fluid, mean protein concentration, and inflammatory cell infiltration of pulmonary tissues when compared to the saline-treated LPS-challenged control. In addition, lung histology of the bergapten-treated LPS-challenged mice showed significantly less oedema, congestion, and alveolar septa thickening when compared to the saline-treated LPS-challenged disease control. LPS-induced oxidative stress was significantly reduced through increased tissue activities of catalase and superoxide dismutase and reduced malondialdehyde levels on treatment with bergapten. In the triple antigen-induced active anaphylaxis, daily administration of bergapten at 3, 10, and 30 mg kg−1 for 10 days, respectively, protected previously sensitized and challenged mice against anaphylactic shock. Overall, our study demonstrates the ability of bergapten to attenuate allergic airway-induced hypersensitivity in murine models of inflammation, suggesting its possible therapeutic benefit in this condition.